The Effect of Non-Routine Geometry Problem on Elementary Students Belief in Mathematics: A Case Study - Khoerul Umam; Kowiyah Kowiyah (JETL (Journal of Education, Teaching and Learning), 2018)
Many learners hold traditional beliefs about perimeter and area that a shape with a larger area must have a larger perimeter while shape with the same perimeter must have the same area. To address this issue, non-routine geometry problem is given. This qualitative descriptive research used to reach the goal and to explore the effect of non-routine geometry problem on elementary student belief in mathematics. The instrument has been developed to accommodate intuitive student belief and student’s belief about the concept of perimeter. The results provide evidence that students’ intuitive belief about perimeter can be change through non-routine geometry problem which is required understanding and some mathematical analysis. Fortunately, the problem has helped the elementary students revise and correct their beliefs, thoughts, and understandings relating to the circumference of shape.